ANALISIS PEMILIHAN MODA TRANSPORTASI UMUM MENUJU STASIUN GAMBIR MENGGUNAKAN TRANSPORTASI ONLINE DAN BUS TRANSJAKARTA - Ferdiansyah, Ridho; Rizani, Mohammad Debby; Yudaningrum, Farida (Jurnal Teknik Sipil Giratory UPGRIS, 2023)
Public transportation acts as a sustainable mode of transportation to reduce the increasing level of pollution and traffic congestion. Public transportation has many types, in Jakarta, for example, online transportation and Transjakarta buses. This study aims to analyze the characteristics of online transportation travellers and Transjakarta buses, analyze the chances of choosing between the two modes of public transportation, and determine the level of service according to the community. Data collection using questionnaires distributed at Gambir station. Characteristics of travelers were analyzed using descriptive statistics. The probability of choosing a mode is analyzed using the binary logit difference model with the help of multiple linear regression equations. The level of service of the two modes of public transportation was analyzed using a Likert scale. The results showed that the characteristics of online transportation travellers are dominated by female, of productive age, highly educated, worked as an employee, earned quite a lot of money, traveled for vacation or recreational purposes, and the reason for choosing the mode was getting to the destination quickly. The characteristics of Transjakarta bus travellers are dominated by male, productive age, highly educated, work as an employee, earn quite high, travel for vacation or recreational purposes, and the reason for choosing the mode is the low price. The dominant choice of public transportation mode is online transportation. The level of online transportation services for the security and convenience aspects is in the good category, and the ease and reliability aspects are in the very good category.Keywords: characteristics of travellers, transportation mode, likert scale